The effect of intravenous vitamin C on clinical outcomes in patients with sepsis or septic shock: A meta-analysis of randomized controlled trials - Zhu, Huiyan; Xu, Xiaoya; Zhang, Kai; Ye, Qiaoping (Frontiers in Nutrition, 2022)
Objectives: Vitamin C deficiency is common among patients with sepsis and has been associated with poor clinical outcomes. Nevertheless, the effect of intravenous (IV) vitamin C for the treatment of sepsis remains controversial. The purpose of this meta-analysis was to evaluate the effect of IV vitamin C in patients with sepsis or septic shock. Methods: Electronic databases (PubMed, Embase, Scopus, and Cochrane Library) were searched from inception through May 25th, 2022 for randomized controlled trials evaluating the effect of IV vitamin C treatment in patients with sepsis. The primary outcome was short-term mortality, and secondary outcomes including the duration of vasopressor, length of intensive care unit (ICU) stay, and Sequential Organ Failure Assessment (SOFA) score after vitamin C treatment. Subgroup analyses were performed based on the type of disease, dose and duration of IV vitamin C. Results: A total of 10 studies were included, with a total sample of 755 septic patients. The IV vitamin C was associated with a significant reduction in the short-term mortality (OR 0.51, 95%CI 0.37 to 0.69, I2=0%) and duration of vasopressor (MD -27.88, 95%CI -49.84 to -5.92, I2=95%). The length of ICU stay (MD -0.68, 95%CI -2.13 to 0.78, I2=74%) and SOFA score (MD -0.05, 95%CI -1.69 to 1.58, I2=86%) were not significantly different between two groups. Conclusion: In patients with sepsis or septic shock, the IV vitamin C reduced the short-term mortality rate and duration of vasopressor, with no effect on the length of ICU stay and SOFA score. Further trials are required to explore the optimal dosage and duration of IV vitamin C.